Experimental investigations on spontaneous combustion of pulverized coal in the oxyfuel combustion system - Takashi KIGA (The Japan Society of Mechanical Engineers, 2020)
CCS (Carbon Dioxide Capture and Storage) is one of the technologies able to adequately displace CO2 from fossil fuel fired power plants and the only technology capable of reducing large-scale emissions. In particular, coal emits a lot of CO2, although it is an important energy resource in terms of energy security. To address this situation, IHI had developed oxyfuel combustion technology to capture CO2 from coal-fired power plants, and the demonstration using a 30MWe unit in Australia was successfully carried out. In order to commercialize the technology widely, how to configure the primary gas system is one of the important examination items. When adding oxygen into the primary gas system, depending on the type of mill, pulverized coal deposited in the mill may ignite spontaneously. To investigate the spontaneous combustion characteristics of the deposited pulverized coal under oxyfuel conditions, therefore, laboratory-scale experiments were carried out. The pulverized coal was deposited in a 100mm square mesh box, and it was installed in a thermostatic chamber. Then the mixed gas of N2/O2 or CO2/O2 was introduced into the chamber, and the temperature in the coal sample was measured. From the results, there was little temperature difference at which spontaneous combustion occurred between N2/O2 and CO2/O2 atmosphere, while there was a tendency that it might be relatively hard to occur under CO2/O2 atmosphere. The results also showed a tendency that the influence of temperature was stronger than the oxygen concentration.